2021
DOI: 10.1021/acs.chemmater.1c02999
|View full text |Cite
|
Sign up to set email alerts
|

Linker Contribution toward Stability of Metal–Organic Frameworks under Ionizing Radiation

Abstract: The effects of radiation on a series of UiO derivative metal−organic frameworks (MOFs) that contain the same zirconium hexamer node and similar organic linkers, UiO-66, UiO-66−NH 2 , UiO-66−OH, and NU-403, were examined using γ-rays and 5 MeV He ions. UiO-66, UiO-66−NH 2 , and UiO-66−OH contain aromatic linkers and are significantly more stable to radiation than NU-403. Of these, UiO-66 is the most radiation resistant, displaying crystalline features up to 47 MGy of He-ion irradiation. MOFs containing aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…A recent paper confirms that UiO-66-NH 2 is able to retain iodine under high radiation, temperature and humidity conditions and that the structure was unaffected. 119 The stability of MOFs when exposed to high levels of radiation [120][121][122] has highlighted the potential for them to be used, not only in the capture of radioactive iodine, but also for long-term storage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper confirms that UiO-66-NH 2 is able to retain iodine under high radiation, temperature and humidity conditions and that the structure was unaffected. 119 The stability of MOFs when exposed to high levels of radiation [120][121][122] has highlighted the potential for them to be used, not only in the capture of radioactive iodine, but also for long-term storage.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent work, we initiated a more methodical approach with both gamma and He ion irradiation by exploring the effect of linker on otherwise isostructural MOFs. 35 We pioneered methods to achieve doses up to 100 MGy, at the frontier of that required to induce X-ray amorphization of the highly connected and stable Zr-based MOFs, determined that ligand aromaticity greatly enhanced radiation resistance, and observed the diminishing effect of electron-donating groups on substituent rings. Vibrational spectroscopy provided insights into the atomic location of MOF radiation damage (i.e., the node-linker connection).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The irradiation of Zr-UiO-66 was not executed in this study as it was recently reported with parallel methodology in a linker-focused study. 35 Because Wang et al 8 observed what they describe as an antenna effect between the metal nodes, which absorb ionizing radiation and transfer the energy to the linkers, and previous work identifies the weakest link as the metal node-linker connection, 35 we hypothesized that the M-UiO-66 radiation stability trend will follow the strength of the individual metal-toligand complexes, a product of Lewis acidity and electronegativity. Islamoglu et al 58 detail the electronic properties of the M-UiO-66 series (where M = Zr, Ce, Hf, and Th) and reveal a spectroscopic indicator for electronegativity-based ligand lability, resulting in the following trend: Hf > Zr > Th > Ce.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This makes it the most radioresistant cluster species reported up to date, and one of the most radiolytically stable metal-organic materials in general. 30,38,[97][98][99][100] As an alternative pathway for preparing photochromic materials, incorporating a stimuli-responsive ligand in the void of a two-dimensional Th-MOF, Th 6 O 4 (OH) 4 (HCOO) 12 (DMF) 2 (Th-SINAP-2) gave rise to a host-guest assembly Htpbz@Th-SINAP-2 (Htpbz = 4-(2,2′:6′,2″-terpyridin-4′-yl) benzoic acid). 46 The high attenuation coefficient of this Th-MOF endows it with a selective photochromic behavior toward X-ray over UV, and its color changes from colorless to green and ultimately to dark yellow upon X-ray irradiation.…”
Section: Perspectivementioning
confidence: 99%
“…This makes it the most radioresistant cluster species reported up to date, and one of the most radiolytically stable metal–organic materials in general. 30,38,97–100…”
Section: Optical and Electronic Applicationsmentioning
confidence: 99%